Estimation of mechanical power and energy cost in elite wheelchair racing by analytical procedures and numerical simulations - Forte, Pedro (2018)
The aim was to compare the mechanical power and energy cost of an elite wheelchair sprinter in the key-moments of the stroke cycle. The wheelchair-athlete system was 3D scanned and then computational fluid dynamics was used to estimate the drag force. Mechanical power and energy cost were derived from a set of formulae. The effective area in the catch, release and recovery phases were 0.41m(2), 0.33m(2) and 0.24m(2), respectively. Drag increased with speed and varied across the key-moments. The catch required the highest total power (range: 62.76-423.46W), followed-up by the release (61.50-407.85W) and the recovery (60.09-363.89W).